Five-Year Impacts of Group-Based Financial Education and Savings Promotion for Ugandan Youth - Horn, Samantha; Jamison, Julian C.; Karlan, Dean; Zinman, Jonathan (The Review of Economics and Statistics, 2026)
Abstract We experimentally evaluate group-based financial education, savings account access, or both for members of Ugandan youth groups. We measure both short- and long-run impacts with one- and five-year endline household surveys. Education, but not account access, increases measured financial knowledge and trust at one year. At five years, knowledge effects essentially disappear, and trust effects weaken. However, savings and income increase for each treatment at both endlines, which is noteworthy given the interventions’ low cost and the long time horizon of our second endline. Exploring potential mechanisms, we find evidence consistent with multiple pathways to behavior change and outcome improvement.